2017
DOI: 10.1038/srep42144
|View full text |Cite
|
Sign up to set email alerts
|

Novel benzoxazole derivatives DCPAB and HPAB attenuate Th1 cell-mediated inflammation through T-bet suppression

Abstract: Interferon-γ (IFN-γ), a critical inflammatory cytokine, is primarily produced by T helper 1 (Th1) cells and accelerates the pathogenesis of inflammatory colitis. Pharmacological suppression of IFN-γ production attenuates dysregulated inflammatory responses and may be beneficial for treating inflammatory disease. In this study, we aimed to discover potent anti-inflammatory compounds that suppress IFN-γ production and found that the novel benzoxazole derivatives, 2-((3,4-dichlorophenyl) amino) benzo[d]xazol-5-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is likely that the 4 → 1 photoisomerization proceeds through a two-step mechanism, involving an initial [1,5] H-atom shift from the hydroxyl group to the isocyano group, originating the nitrile ylide derivative 6, followed by cyclization of this intermediate to form 1. The energy profile for the conversion of nitrile ylide 6 to benzoxazole 1 is presented in Figure 3.…”
Section: Photochemistry Of Matrix-isolated Benzoxazolementioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the 4 → 1 photoisomerization proceeds through a two-step mechanism, involving an initial [1,5] H-atom shift from the hydroxyl group to the isocyano group, originating the nitrile ylide derivative 6, followed by cyclization of this intermediate to form 1. The energy profile for the conversion of nitrile ylide 6 to benzoxazole 1 is presented in Figure 3.…”
Section: Photochemistry Of Matrix-isolated Benzoxazolementioning
confidence: 99%
“…1,3-Benzoxazole 1 (also known as benzo­[ d ]­oxazole or benzoxazole) consists of an oxazole ring fused to a benzene ring (Scheme ). It is the nucleus of numerous compounds with important biological, pharmacological, and photophysical properties. Its isomeric 1,2-benzisoxazole 2 (also known as benzo­[ d ]­isoxazole or benzisoxazole) has an isoxazole ring fused to a benzene ring (Scheme ). They differ by the relative position of the oxygen and nitrogen atoms: in oxazole, the two heteroatoms are separated by a carbon atom, while in isoxazole, they are bound directly.…”
Section: Introductionmentioning
confidence: 99%
“…agonist [20], was found to suppress IFN-γ production in activated human peripheral blood mononuclear cells through suppression of expression of T-bet, which is the master transcription factor of Th1 differentiation [21]. A recent study reported that some benzoxazole derivatives could suppress IFN-γ production in murine CD4 + T cells in a similar manner to clozapine [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, clozapine, which can function as an H 4 agonist [19], was found to suppress IFN-γ production in activated human peripheral blood mononuclear cells through suppression of expression of T-bet, which is the master transcription factor of Th1 differentiation [20]. A recent study reported that some benzoxazole derivatives can suppress IFN-γ production in murine CD4 + T cells in a similar manner to clozapine [21]. Accumulating evidence suggests that T-bet is involved in IFN-γ production both in CD4 + and CD8 + T cells, although T-bet-independent IFN-γ production was reported in CD8 + T cells [22,23,24].…”
Section: Discussionmentioning
confidence: 99%